Application of Management Approach on Two Animal Tales: (Pengaplikasian Pendekatan Pengurusan terhadap Dua Buah Cerita Binatang) (Malay Literature, 2021)
Most audiences often question the importance of studying Malay literature in life. With the assumption of most audiences that it is not important to study Malay literature because Malay literature has no value in life. As a result, Malay literature was marginalized. But in reality, a lot of knowledge can be gained when studying Malay literature. Among them are medical knowledge, law, customs, culture, arts and no less important is management knowledge. In this article, the author will prove that in Malay literature there is an element of management. An element that is no less important in human life. This study uses a qualitative method, which is to analyze literary works. The approach used in this study is a management approach. This article will comprehensively explain the management approach, which covers the definition and principles of management, namely planning, organizing, leadership, staffing and control. Furthermore, the author will analyze the literary work by applying the management approach to two animal stories, namely "Giants at War with Elephants" and Hikayat Pelanduk Jenaka (Sheikh Alam Berlawan dengan Raksasa). Furthermore, a comparison of competencies and weaknesses in organization of management is made for both tales. It was found that the organization in the story "Giants at War with Elephants" is more organized and orderly when compared to the organization in the story Hikayat Pelanduk Jenaka (Sheikh Alam Berlawan dengan Raksasa). The study of management approach in literary analysis not only makes Malay literature interesting, but also can educate and make the public aware of the importance of management in building human life in an organized and orderly manner.